An exploration of the principal's role on learner achievement : a case study of two Soweto secondary schools. - Ginya, Lindiwe Angel (My University, 2013)
The poor matric results currently in the Soweto Township Secondary Schools are a cause for concern. This study aims to explore and understand the role of the principal on learner achievement. It transpired from the reviewed literature that the instructional leadership theory was helpful in providing insights into understanding issues of principals leading or supporting learner achievement efforts within the school context. This study relied on in-depth taped interviews with school principals, curriculum deputy principals and focus group discussions with the Representative Council of Learners (RCL), together with the documentary analysis to answer the research question and sub–questions. The sample schools were selected purely on the previous, “academic excellence.” This study also investigated what students, teachers and deputy principals perceive principals to do to influence learner achievement. The study discovered that the scope of principals‟ influence on learner achievement varies from one school to the next. The influence was both direct and at times mediated. The findings were that instructional leadership was a dominant style of leadership in the schools studied, as students identified direct and highly influential instructional leadership behaviours. It also transpired that the critical role of the principal to influence and enhance learner achievement was to manage teaching and learning, which is the core business of the school.
Keywords: High school principals--South Africa--Soweto.; Educational leadership--South Africa--Soweto.; Academic achievement--South Africa--Soweto.